Therapeutic potential of mangiferin against kidney disorders and its mechanism of action: A review - Lum, Pei Teng; Mahendran, Sekar; Gan, Siew Hua; Jeyabalan, Srikanth; Bonam, Srinivasa Reddy; Nur Najihah, Izzati Mat Rani; Ku-Marina, Ku-Mahdzir; Seow, Lay Jing; Wu, Yuan Seng *; Vetriselvan, Subramaniyan; Fuloria, Neeraj Kumar; Fuloria, Shivkanya (Elsevier, 2022)
There is a swing in research developments concerning the utilization of natural products as effective pharmacotherapeutic agents due to their comparatively lower toxicities than synthetic compounds. Among natural products, mangiferin is a natural C-glucosyl xanthonoid polyphenol with remarkable pharmacological activities. Emerging evidence indicates the therapeutic benefits of mangiferin against various kidney disorders, including renal injury, diabetic nephropathy, renal fibrosis, hyperuricemic nephropathy, and lupus nephritis, in experimental animal models. The mangiferin induced antioxidant response resulting in vital functions, such as protection against renal inflammation, inhibits renal cell apoptosis, activates autophagy, causes immunomodulation, regulates renal urate transporters and modulates cell signalling pathways. The purpose of this review provide a brief overview of the in vitro/in vivo reno-protective effect of mangiferin and the underlying mechanism(s) in protecting against kidney disorders. Understanding the pharmacological actions of mangiferin is prominence due to its excellent therapeutic potential in managing kidney disorders. Thus, in addition to this review, in-silico molecular docking is performed against nuclear factor kappa B (NF-κB) and soluble epoxide hydrolase (sEH) to study the mechanism of action of mangiferin. It is believed that mangiferin is a safe reno-protective molecule. The observed positive effects are attributed to the inhibition of inflammation caused by NF-κB and sEH upregulation and oxidative stress activation. Studies on the efficacy and safety of mangiferin in clinical trials are further warranted to confirm its medicinal potential as therapeutic agent for kidney disorders in humans.